Form Follows Meaning: An Analysis of the “Istana Garuda” Design through the Lens of Mimesis - Rahmawati, Anna Lucy (Cultural Arts Research and Development, 2024)
This article analyzes the design of Istana Garuda as a representative example of mimetic practice in architecture. Since being announced as the winning design in 2021, it has attracted public attention and sparked debate due to its resemblance to Indonesia’s national symbol, the Garuda. The controversy is not only about its aesthetic and the building form and function validity but also questions the credibility of its designer, I Nyoman Nuarta, who, rather than an architect, is a professional sculptor. It is interesting because, in his design, Nuarta draws upon the Garuda symbol as a source of meaning and form, integrating it with the concept of “Archsculpt” to bridge aesthetic and pragmatic functions. This article aims to demonstrate that architecture, like other art forms, is a mimetic practice rooted in meaning. By adopting a mimetic approach, this article presents an analytical framework of form follows meaning in the design of the Istana Garuda. Through the lens of mimesis, this study emphasizes two important points: (1) the design of Istana Garuda is the result of an architectural process that foregrounds meaning rather than merely imitating the Garuda’s form, and (2) the mimetic approach can serve as an effective tool for creating architectural works that not only reinforce national identity but also preserve Indonesia’s profound cultural values.